2021
DOI: 10.1016/j.regsciurbeco.2020.103596
|View full text |Cite
|
Sign up to set email alerts
|

Population density and urban air quality

Abstract: We use panel data from Germany to analyze the effect of population density on urban air pollution (nitrogen oxides, particulate matter and ozone). To address unobserved heterogeneity and omitted variables, we present long difference/fixed effects estimates and instrumental variables estimates, using historical population and soil quality as instruments. Our preferred estimates imply that a one-standard deviation increase in population density increases air pollution by 3-12%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 48 publications
1
38
1
Order By: Relevance
“…The figure reveals the positive correlation of population density with AQI (correlation coefficient, r = 0.50, p < 0.05), PM2.5 (r = 0.59, p < 0.01), and NO2 (r = 0.55, p < 0.05). Borck and Schrauth (2021) argued the effect of population density on urban air pollution in over 400 German districts. They found that increasing population density by one percent increases NO2 by 0.25 percent, PM10 by 0.07 percent, and AQI with an elasticity of 0.11-0.13.…”
Section: Resultsmentioning
confidence: 99%
“…The figure reveals the positive correlation of population density with AQI (correlation coefficient, r = 0.50, p < 0.05), PM2.5 (r = 0.59, p < 0.01), and NO2 (r = 0.55, p < 0.05). Borck and Schrauth (2021) argued the effect of population density on urban air pollution in over 400 German districts. They found that increasing population density by one percent increases NO2 by 0.25 percent, PM10 by 0.07 percent, and AQI with an elasticity of 0.11-0.13.…”
Section: Resultsmentioning
confidence: 99%
“…To conduct this investigation, we utilized the largest collection of Google Street View images that has been leveraged for public health research to characterize neighborhood environments. In examining associations between built environment characteristics and COVID cases, we controlled for demographic compositional characteristics of areas and population density, which has previously been utilized in econometric studies as a proxy for air pollution and other factors found with greater prevalence in urban areas [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another systematic study on 109 districts in Germany, which included 51 urban districts, Borck and Schrauth [14] found that a 1% increase in population density increased PM 2.5 concentrations by a modest 0.08%. Using an authoritative survey, Ahlfeldt and Pietrostefani [27] cited both studies by Carozzi and Roth [13] and Borck and Schrauth [14], and recommended +0.13 as the elasticity for pollution reduction. In short, the impact of high-density cities on PM 2.5 pollution was positive in Chinese studies.…”
Section: Literature Review Of Pm 25 Concentrations In Urban Centersmentioning
confidence: 97%
“…In terms of developed countries, PM 2.5 is not as critical of an environmental pollution issue for cities in developed countries [2]. Thus, only a few socio-economic studies on PM 2.5 concentrations for cities in developed countries have been published recently on cities in the U.S. [13] and Germany [14]. A group of related studies on air pollution in developed countries such as the U.S. and Canada have also been published [16][17][18][19][20][21].…”
Section: Literature Review Of Pm 25 Concentrations In Urban Centersmentioning
confidence: 99%
See 1 more Smart Citation